" La Administración Fiduciaria y su incidencia frente a la condición suspensiva del Testamento, en enlace negocios fiduciarios en la ciudad de Quito, año 2015" - Aragadbay Ola, Jessica Janeth (2016)
This research aims to analyze the power of causing dispose of property after death, anticipating that this action is not always easy, because in the testament there may be a condition that prevents the domain of the tested goods and in fact subordinated to do something simple criterion established by the testator. Therefore, while the condition is not met, there is no transfer of domain to the inheritor, and for that reason, there is a need to determine a way in which such property will be safeguarded. It is common that an executor, custody assets when it comes to property or furniture that do not deteriorate, however, where the estate includes business management, or goods that can deteriorate, there is a need to entrust to a trust, to be responsible for their care. Therefore, the present investigation is initiated, arguing that the trusteeship that constitutes the event of the suspensive condition of the testament, it has diverse backgrounds, same as will be discussed below.